Peripheral facial paralysis as initial manifestation of hypertension in a child - Aynacı, F. Müjgan; Şen, Yaşar (The Turkish Journal of Pediatrics, 2002)
Hypertension is one of the rare causes of peripheral facial paralysis in children. The unawareness of this association at presentation may cause serious medical errors and result in delays in the diagnosis of hypertension, which may worsen with corticosteroid therapy given for Bell’s palsy. We describe a severely hypertensive child who was first seen with peripheral facial paralysis and given corticosteroid therapy in another hospital. She presented to our clinic during the second facial paralysis attack with hypertensive pontine hemorrhage.